Massive upper gastrointestinal bleeding caused by an intercostal arterio-esophageal fistula: A rare case report - Yang, Kai-Chun (Radiol Case Rep, 2020)
Arterio-esophageal fistula (AEF) is a rare life-threatening cause of upper gastrointestinal bleeding. Realizing the risk factors and clinical presentations of AEF will enable us to provide timely diagnosis, efficient treatment, and better outcome. We present a 43-year-old Taiwanese man who had histories of destructive lung, innominate artery-trachea fistula, and received bilobectomy. He was admitted to our hospital with fresh blood drainage from nasogastric tube. He was diagnosed as right fifth intercostal artery esophageal fistula by computed tomography angiography and transcatheter arterial embolization was performed. The bleeding stopped and the patient was discharged uneventfully. The risk factors of AEF include esophageal foreign body, vascular surgery, thoracic arterial malformations, and concurrent chemoradiotherapy in T4-esophageal cancer. Computed tomography angiography may be the most sensitive diagnostic test. Transcatheter arterial embolization or endovascular stent grafting may be considered as the first-line treatment of AEF in the future.